Seventh-Day Syndrome after liver transplantation in a patient with hepatocellular carcinoma - S. E. Voskanyan; V. S. Rudakov; V. E. Syutkin; A. I. Sushkov; S. V. Lishchuk; A. N. Bashkov; K. K. Gubarev; A. N. Pashkov; A. I. Artemyev (Трансплантология (Москва))
Background. Seventh-Day Syndrome following liver transplantation is a rare but serious complication characterized by a sudden deterioration of the graft function after initial normalization, often leading to death. The peak occurrence of this syndrome is in the late first or early second week post-transplant. Currently, there are no established treatment standards for Seventh-Day Syndrome, and its natural course usually results in a graft loss.Objective. To present a clinical case of Seventh-Day Syndrome after liver transplantation and analyze strategies for early diagnosis and treatment.Results. A patient who underwent liver transplantation for viral cirrhosis and hepatocellular carcinoma was diagnosed with Seventh-Day Syndrome on the eighth day post-surgery, which was accompanied by acute deterioration in the graft function and the development of fulminant liver failure. Despite a timely diagnosis and immediate treatment, including high doses of methylprednisolone, immunoglobulin administration, and plasmapheresis, the patient's condition persistently worsened, resulting in death on postoperative day 11.Conclusion. Despite a timely diagnosis and treatment, the prognosis for Seventh-Day Syndrome remains poor, underscoring the need for further research.